2017
DOI: 10.1371/journal.pone.0175040
|View full text |Cite
|
Sign up to set email alerts
|

Depression-related difficulties disengaging from negative faces are associated with sustained attention to negative feedback during social evaluation and predict stress recovery

Abstract: The present study aimed to clarify: 1) the presence of depression-related attention bias related to a social stressor, 2) its association with depression-related attention biases as measured under standard conditions, and 3) their association with impaired stress recovery in depression. A sample of 39 participants reporting a broad range of depression levels completed a standard eye-tracking paradigm in which they had to engage/disengage their gaze with/from emotional faces. Participants then underwent a stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 50 publications
5
35
0
Order By: Relevance
“…The data show a difference in dilation due to real versus placebo stimulation, denoting an adjustment in sympathetic nervous system in response to tDCS. Prior studies using excitatory NIBS over the right DLPFC showed adverse effects on emotional attention (e.g., increased attention towards negative stimuli, reduced attentional control over emotional information; [14,41,[58][59][60]), which in turn is suggested to contribute to maladaptive emotion regulatory processes [42,61]. These findings would be consistent with the notion that excitatory right DLPFC stimulation contributes to decreased cognitive resource allocation to process emotional information, impeding individuals' capacity to engage in emotion regulatory processes.…”
Section: Discussionsupporting
confidence: 77%
“…The data show a difference in dilation due to real versus placebo stimulation, denoting an adjustment in sympathetic nervous system in response to tDCS. Prior studies using excitatory NIBS over the right DLPFC showed adverse effects on emotional attention (e.g., increased attention towards negative stimuli, reduced attentional control over emotional information; [14,41,[58][59][60]), which in turn is suggested to contribute to maladaptive emotion regulatory processes [42,61]. These findings would be consistent with the notion that excitatory right DLPFC stimulation contributes to decreased cognitive resource allocation to process emotional information, impeding individuals' capacity to engage in emotion regulatory processes.…”
Section: Discussionsupporting
confidence: 77%
“…Supporting this assumption, depressed compared to healthy individuals are characterized by a reduced attention processing of positive social signals, such as others' happy faces (Armstrong & Olatunji, 2012), and conversely by an increased attention processing of negative social signals, such as others' sad and disgusted faces (Armstrong & Olatunji, 2012;Sanchez, Vazquez, Marker, LeMoult, & Joormann, 2013;Sanchez, Romero & De Raedt, 2017). These attentional biases have been shown to contribute to inefficient behavioral and emotional regulation during social interactions (Sanchez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These attentional biases have been shown to contribute to inefficient behavioral and emotional regulation during social interactions (Sanchez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is an absence of the protective bias usually observed in healthy subjects. Although preliminary data suggest a slower engagement with positive stimuli in depressed participants compared to non-depressed participants [11], the very nature of the attentional components involved in anhedonic bias remains poorly understood.…”
Section: Introductionmentioning
confidence: 98%